Procedures and Obstacles to Implementing the Write-off of Non-Operating Fixed Assets and Their Impact on Depreciation Costs at PT. PLN (Persero) - Nadia Salsabila Putri Ayuda; Kartini Kartini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The development of the economy and business sector in every country in the world is a trigger for competition between companies to gain profit. This competition raises demands for the relevance and reliability of the company's financial reports that are sustainable, which are intended to avoid conflict between users of financial reports, both internally and externally, so that proper company management is needed in managing the components in the company. This writing is a descriptive qualitative research in the form of observation, interviews and documentation at PT PLN (Persero). Based on the data found that non-operating assets are still included in the status of operating assets and if not immediately proposed will increase the accumulated depreciation costs. Depreciation costs are one of the elements of the company's operational costs that affect the company's profit because they reduce revenue. In addition to depreciation costs, there are also costs that will have an impact, namely the cost of maintaining warehouse operations. Therefore, the company must develop a more efficient and effective strategy to manage these non-operating assets so as not to burden operations and financial performance in the long term. Thus, it is concluded that in the implementation of the asset management system there are still various obstacles in the form of incomplete administrative data and assets that have not been neatly inventoried and external obstacles such as irregular material returns that further complicate asset data management. So the author makes a recommendation, namely the implementation of an integrated asset digitalization system to help track the condition and location of assets more accurately, to speed up the identification process.